Redeeming Politics - Kaufman, Peter Iver. (Princeton : Princeton University Press, 2014)
Peter Iver Kaufman explores how various Christian leaders throughout history have used forms of ""political theology"" to merge the romance of conquest and empire with hopes for political and religious redemption. His discussion covers such figures as Constantine, Augustine, Charlemagne, Pope Gregory VII, Dante, Zwingli, Calvin, and Cromwell. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperbac.
Print version record.
Cover.
Keywords: Christianity and politics -- History of doctrines; Church and state -- History; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; Christianity and politics -- History of doctrines; Church and state; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books; History